An Unusual Neonatal Presentation of Scimitar Syndrome - Abdul Aziz, Ahmad; Thomas, Sumesh; Lautner, David; Al Awad, Essa Hamadan (American Journal of Perinatology Reports, 2018)
Scimitar syndrome is characterized by partial or total anomalous pulmonary venous return from the right lung along with pulmonary hypoplasia. We present a case of a 37 weeks' gestation male infant with antenatal ultrasound findings of suspected partial anomalous pulmonary venous return (PAPVR) and coarctation of the aorta. The newborn presented with respiratory distress, a chest X-ray and chest computed tomography (CT) angiogram confirmed the diagnosis of scimitar syndrome. The combination of scimitar syndrome with aortic coarctation is extremely rare with only a few cases previously reported.
Keywords: neonatology; perinatology; pediatric cardiology; pulmonology